On-line satellite-assisted tools for participatory irrigation water management - Osann A.; Calera A. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
We briefly present the concept and some applications of irrigation water management assisted by Earth observation satellites and information and communication technologies. Jointly, these tools provide easy-to-use access to information on key parameters for monitoring and management of irrigation schemes, farms, and river basins.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)